INDIAN COUNTER INSURGENCY APPROACH IN KASHMIR A FACTOR OF HUMAN CONCERN: CRITICAL ANALYSIS - Reshi, Basharat Nazir; Bhat, Mukhtar Ahmad; Ain, Qurat ul (International Journal of Psychosocial Rehabilitation, 2020)
The period of 1990s witnessed the rise of militancy as reaction against the failure of India state to allow the democratic values flourished in Kashmir. The policy of Indian state to control the affairs of Jammu And Kashmir State by compromising the democratic principles frustrated the common masses in Jammu and Kashmir. The lack of implementation of democratic principles provides an opportunity to national conference to establish a dictatorial rule by either supressing or not allowing the democratic the dissent voices to flourish in Jammu and Kashmir. The condition of hopelessness and frustration resulted in the origin of the period of militancy in Jammu and Kashmir. As the lawlessness prevailed due to the rise of violence level posed a serious challenge for the national security of India. The Indian state decided to start a tough counter insurgency campaign to up root the threat of militancy which has posed a challenge for national security. The military campaign of Indian state receives criticism due to the gross root human right violations at the hands of security forces. The main objective of the paper is to analyse the counter insurgency campaign of India and its implications for human rights.